TUGAS DEWAN PASTORAL STASI DALAM PARTISIPASI HIDUP MENGGEREJA UMAT DI STASI SANTO JOHANNES PANSUR BATU PAROKI SANTO FIDELIS DOLOK SANGGUL - Johannes Sohirimon Lumbanbatu (STP St. Bonaventura Medan, 2019)
The task of the Stasi Pastoral Council in congregational participation is very important for church life for the congregation in the station. The Stasi Pastoral Council functions to develop the church life of the people, providing guidance, direction, motivation for a pastoral approach through visits to the homes of the people so that they are also able to develop their church life through participation in the areas of liturgy, diakonia, coinsonia, kerygma and martyria. People can also understand what their true duties as God's people are, namely, being Imams. Kings and Prophets in a church or in the midst of society. This was done by the Stasi Pastoral Council management to meet the needs of the people at the station, so that their church life could develop and harmonious relations could be established between the station management and the people, as well as in the community